Balans na linie – kilka uwag o polskich reformach oświaty - Szymański, Mirosław J. (Studia Edukacyjne, 2019)
The closer we get to our times, the more often school reforms take place in different countries. They are an attempt to respond to deep social changes. However, in most cases, these reforms are not very effective. The author gives examples of failed Polish educational reforms of the last half-century. It is noted that there was a large gap between the façade proclamations of the benefits that the announced reforms were supposed to bring and their real effects. Therefore, the author puts forward a thesis that too often reformers play a confidence game and in fact the announced change in education means no change in practice. Meanwhile, real, profound school reforms are essential, as society and the economy will increasingly need graduates educated to meet the needs of the 21 st century. They are supposed to be people who think critically, are creative, have high communication skills, and are focused on cooperation with others. For the preparation of such graduates to be possible, there needs to be a radical change in the concept of the school and in the way teachers work.